Preservation Of Coping Strategies Of Women In The Merapi Disaster Area From Educational Perspectives On Covid-19 Pandemic - Sri Suryanti, Hera Heru; Widiastuti (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2023)
The educational level that a person has is one of the means for that person to exist in society. The educational level affected thewomen to determine coping strategies after the Mount Merapi disaster. When the Covid-19 pandemic occurred, the womenfaced difficulties in earning living . This study aims to investigate how to preserve the coping strategies of women in the MountMerapi disaster area from the perspective of education during the 2020 Covid-19 pandemic. The study was conducted in thesurrounding area of Mount Merami such as Boyolali, Klaten, Magelang, and Sleman in 2020-2021. A descriptive qualitativeresearch method was employed in this study where the subjects involved were women affected by the Mount Merapi disaster.The research object was the preservation of coping strategies from an educational perspective on the Covid-19 pandemic. Datawere collected using interviews, observations, Focus Group Discussions (FGD), and documentation. The validity of the datawas obtained using extended observations, research persistence, triangulation, peer discussion, and negative case analysis. Datawere analyzed using interactive analysis. The results of the study were as follows: women affected by the Mount Merapi disasterwith low education tend to preserve coping strategies following family livelihoods and self-confidence; those with secondaryeducation (junior high school, high school) preserve coping strategies based on increasing income but were less daring to try newthings; meanwhile, highly educated people brave to take new steps to restore the economy and brave to urge the public not topreserve coping strategies that can have a negative impact in the future. In conclusion, the coping strategies employed by womenaffected by the Mount Merapi disaster from the perspective of education during the Covid-19 pandemic varied according to theirlevel of education and beliefs as well as the legacy of their family habits.Keywords: Coping Strategies, Educational Level, Covid-19